Política monetaria y la tasa de interés de las grandes empresas - Roca Garay, Richard (2011)
This work analyze the behavior of cost of credit of best enterprises for the period 2003-2011 which is known as corporate rate and is determined basically by the interest rate that the Central Bank fix each month in Peru.